Pengaruh Bentuk Penampang Kolom Terhadap Perilaku Elemen Struktur - Husna, Riska Jannatul; Silviana, Merry; zardi, Muhammad (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Generally, a building structure planning in Indonesia, both office buildings and other buildings, uses a square-shaped column design as a force buffer for the main beams, but in some conditions there are also buildings that use round columns as the main structure. The purpose of this thesis is to determine the influence of the existing column cross-sectional shape used in the Banda Aceh District Court Building and the circular column cross-sectional shape on the basic seismic shear force and the deviation between levels. The Banda Aceh District Court Building is planned to have 3 floors with a building area of 4,800 m2. The research process carried out is quantitative in nature where it begins with the collection of data on the structure and drawings of the building. The final project research method uses Etabs v21 and spColumn software where the structure analysis only includes the column structure. The earthquake load was calculated using the equivalent static method based on SNI 1726-2019. From the results of the analysis obtained from spColumn , the existing column cross-sectional shape used in the District Court Building has a basic seismic shear force of 7639.995 kN for the X direction and 7639.994 kN for the Y direction. The existing column cross-sectional shape used in the District Court Building has an elastic drift value of ex 1.195 mm, a daney value of 0.875 mm, an inelastic drift value of 6.573 mm and a y value of 4.813 mm. For the shape of the cross-section of the round column, the value of elastic drift ex is 3.199 mm and ey 2.718 mm, the value of inelastic drift x 17.595 mm and y is 14.949 mm, where from the results of the calculation of the deviation between the levels does not exceed the drift limit value of the two cross-sectional forms of the column.